Use of UGC-Infonet e-Journals by Research Scholars of Manipur University, Manipur: A Study / Bobby Phuritsabam, Th Purnima Devi and Memori Sagolsem - Bobby, Phuritsabam; Th, Purnima Devi; Sagolsem, Memori (2011)
At the higher education everyone needs advanced & scholar's literature to improve the quality of study and research. The UGC (University Grants Commission) has entered into alliances with publishers for adapting a consortia-based approach for e-journals. UGC-INFONET (University Grants Commission - Information network) is an innovative project launched by UGC to facilitate scholarly e-resources to Indian researchers. With globalization of education and competitive research the demand for the journals has increased over the year. Increase in journal costs, depliting library budgets and drastic cut in number of journals has lead to "journal crisis". On this background the UGC- Infonet is indeed a boom for higher education in India. On 29th January 1993 Inflibnet select Manipur University (MU) as one of the eleven Inflibnet nodes of India in the first phase. Under this programme Manipur University can access the union database as well as 5000 journals. The main objective of the study is to find out the perspective and attitudes of users towards e-journals, to analysed the use and users of e-journals, to study the impact and use of e-journals by the researchers, to know the awareness of the e-journals by the researchers, to find out the significance of e-journals over print, to find out the problem faced by the research scholars in accessing. Proposed study adopted questionnaire method to collect relevant data. A total of 270 responded out of 300 distributed questionaire. The finding reveals that 93% of the researchers covered undre study has knowledge about UGC Infonet. E-journals are having positive impact